Impact of ESG Implementation on Financial Performance and Capital Structure - Gabriella Alodia Jovita (Jurnal Informatika Ekonomi Bisnis, 2023)
The realization of investments in Indonesia has surpassed 23.3% of the targeted amount for the year 2023, indicating a gradual economic recovery. This creates an opportunity for companies to attract more investors. The high level of investment is followed by certain responsibilities named Environmental, Social, and Governance (ESG) within their operational businesses. The implementation of ESG in Indonesia is further supported by the Indonesia Government through the Financial Services Authority Regulation No. 51/POJK.03/0217 and the establishment of the Carbon Exchange regulation in 2023. The objective of this study is to discern the influence of company ESG scores on companies’ performance, measured through ROE and its capital structured, measured by DER. ESG data were obtained through access to Refinitiv Eikon, incorporating data from all sub-points within the three ESG aspects. The study population is companies listed on the Kompas100 index. Under the purposive sampling method, twenty-six companies have disclosed their ESG and financial data for the year 2017-2022. Statistical processing of data was conducted using SEM-PLS. The study concludes that E, S, and G scores individually influence ROE but do not have any significant impact on DER. This study offers insight to assist companies in formulating ESG implementation strategies, with a focus on environmental innovation for E aspect, product responsibility for the S aspect, and shareholder considerations for the G aspect.